The role of Size-Specific Dose Estimate (SSDE) in patient-specific organ dose and cancer risk estimation in paediatric chest and abdominopelvic CT examinations - Franck, Caro; Vandevoorde, Charlot; Goethals, Ingeborg; Smeets, Peter; Achten, Eric; Verstraete, Koenraad; Thierens, Hubert; Bacher, Klaus (European radiology, 2016)
Objectives To develop a clinically applicable method to estimate patient-specific organ and blood doses and lifetime attributable risks (LAR) from paediatric torso CT examinations. Methods Individualized voxel models were created from full-body CT data of 10 paediatric patients (2–18 years). Patient-specific dose distributions of chest and abdominopelvic CT scans were simulated using Monte Carlo methods. Blood dose was calculated as a weighted sum of simulated organ doses. LAR of cancer incidence and mortality were estimated, according to BEIR-VII. A second simulation and blood dose calculation was performed using only the thoracic and abdominopelvic region of the original voxel models. For each simulation, the size-specific dose estimate (SSDE) was calculated. Results SSDE showed a significant strong linear correlation with organ dose (r > 0.8) and blood dose (r > 0.9) and LAR (r > 0.9). No significant differences were found between blood dose calculations with the full-body voxel models and the thoracic or abdominopelvic models. Conclusion Even though clinical CT images mostly do not cover the whole body of the patient, they can be used as a voxel model for blood dose calculation. In addition, SSDE can estimate patient-specific organ and blood doses and LAR in paediatric torso CT examinations. Key Points • Blood dose can be simulated using the patient’s clinical CT images. • SSDE estimates patient-specific organ/blood dose and LAR in paediatric CAP CT-examinations. • SSDE makes on-the-spot dose and LAR estimations possible in routine clinical practice.